2000
DOI: 10.1016/s1097-2765(00)80262-2
|View full text |Cite
|
Sign up to set email alerts
|

Female Mice Heterozygous for IKKγ/NEMO Deficiencies Develop a Dermatopathy Similar to the Human X-Linked Disorder Incontinentia Pigmenti

Abstract: IKK gamma/NEMO is the essential regulatory subunit of the I kappa B kinase (IKK), encoded by an X-linked gene in mice and humans. It is required for NF-kappa B activation and resistance to TNF-induced apoptosis. Female mice heterozygous for Ikk gamma/Nemo deficiency develop a unique dermatopathy characterized by keratinocyte hyperproliferation, skin inflammation, hyperkeratosis, and increased apoptosis. Although Ikk gamma+/- females eventually recover, Ikk gamma- males die in utero. These symptoms and inherita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
303
1
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(320 citation statements)
references
References 36 publications
13
303
1
2
Order By: Relevance
“…Retrovirus constructs containing C-terminal Flag epitope-tagged HHV8 vFLIP (K13-Flag) were generated in MSCVneo and MIGR1-based retroviral vectors (Pear et al, 1998) and amphotropic viruses generated and used for infection as described previously . The IKKaÀ/À and IKKbÀ/À mouse embryonic fibroblast cells were generated in Dr Inder Verma's laboratory (Li et al, 1999a, b) and IKKg/NEMOÀ/À cells were generated in Dr Michael Karin's laboratory (Makris et al, 2000). These cells were kindly provided by Dr Richard Gaynor and were maintained in DMEM supplemented with 10% FBS.…”
Section: Plasmids Cell Lines and Reagentsmentioning
confidence: 99%
“…Retrovirus constructs containing C-terminal Flag epitope-tagged HHV8 vFLIP (K13-Flag) were generated in MSCVneo and MIGR1-based retroviral vectors (Pear et al, 1998) and amphotropic viruses generated and used for infection as described previously . The IKKaÀ/À and IKKbÀ/À mouse embryonic fibroblast cells were generated in Dr Inder Verma's laboratory (Li et al, 1999a, b) and IKKg/NEMOÀ/À cells were generated in Dr Michael Karin's laboratory (Makris et al, 2000). These cells were kindly provided by Dr Richard Gaynor and were maintained in DMEM supplemented with 10% FBS.…”
Section: Plasmids Cell Lines and Reagentsmentioning
confidence: 99%
“…Eda signaling and Troy are believed to be mediated by NF-B (Kojima et al, 2000;Yan et al, 2000;Kumar et al, 2001). Indeed mutations in certain components of the NF-B pathway have molar cusp abnormalities (Hu et al, 1999b;Li et al, 1999;Takeda et al, 1999;Makris et al, 2000;Zonana et al, 2000;Dö ffinger et al, 2001; Ohazama et al, manuscript submitted for publication). Trafs are known mediators of TNF signaling, acting as intracellular adaptor molecules that bind to TNF receptors.…”
Section: Tooth Phenotype In Traf6 Mutant Micementioning
confidence: 99%
“…Gene-targeting experiments have clearly demonstrated that NEMO is absolutely critical for proinflammatory activation of IKK. In fact, NEMO-deficient cells lack detectable NF-B binding activity in response to TNF␣, IL-1␤, and LPS, and they do not show stimulusdependent I B kinase activity (9)(10)(11).…”
mentioning
confidence: 99%